(Ultra) High Pressure Homogenization for Continuous High Pressure Sterilization of Pumpable Foods – A Review - Georget, Erika; Miller, Brittany; Callanan, Michael; Heinz, Volker; Mathys, Alexander (Frontiers in Nutrition, 2014)
Bacterial spores have a strong resistance to both chemical and physical hurdles and create a risk for food industry which has been tackled by applying high thermal intensity treatments to sterilize food. These strong thermal treatments lead to reduction of the organoleptic and nutritional properties of food and alternative are actively searched for. Innovative hurdles offer an alternative to inactivate bacterial spores. In particular, recent technological developments have enabled a new generation of high pressure homogenizer working at pressures up to 400 MPa and thus opening new opportunities for high pressure sterilization of foods. In this short review, we summarize the work conducted on (ultra)-high pressure homogenization (U)HPH to inactivate endospores in model and food systems. Specific attention is given to process parameters (pressure, inlet and valve temperatures). This review gathers the current state of the art and underlines the potential of UHPH sterilization of pumpable foods while highlighting the needs for future work.